EFEKTIVITAS LATIHAN SELF-COMPASSION TERHADAP TINGKAT INSECURE PADA KARYAWAN GEN Z - Aufa Muti’ Amalia; Rava Zakilla Cahyono; Farrin Venonisya Niagara; Lely Nur Azizah; Ni Wayan Sukmawati Puspitadewi (CV. ADIBA AISHA AMIRA, 2026)
Generation Z, which is beginning to dominate the workforce, frequently faces psychological pressure due to social comparison phenomena on social media. This condition triggers feelings of inadequacy (insecurity) that can hinder job performance and psychological well-being within organizations. This study aims to examine the effectiveness of self-compassion training in reducing insecurity levels among Generation Z employees. The method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines, analyzing 18 relevant scientific articles from the PubMed and Scopus databases within the 2021-2026 timeframe. The analysis results indicate that self-compassion serves as a crucial mediator and a